VIA (Visual inspection with acetic acid) and VILI (Visual inspection with lugol’s iodine) as an initial approach with colposcopy as a next screening tool with its positive predictive value in low socioeconomic patients - Paswan, Anita; Kumar, Anil; Jha, Kumudini; Sinha, Shail Kumari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical Cancer is the second most common cancer in women worldwide and India alone contribute the 1/4th of the world’s cases of cervical cancer. In view to this huge burden there was need to establish a feasible screening programme to detect cervical carcinoma at earliest in developing country. Methods: This is a prospective study of 500 women who fulfil the selection criteria. 50 pregnant patients for VIA (Visual inspection with acetic acid), 50 pregnant patients for VILI (Visual inspection with lugol’s iodine) and 400 non-pregnant women for VIA, VILI and colposcopy were enrolled. In positive cases, cervical biopsy with histopathological examination was done. The sensitivity, specificity and positive predictive value of each test were obtained and compared. Chi-square (X2) test was used to test the significance of difference between two proportions of a quantitative data. Results: The sensitivity, specificity, positive predictive value and negative predictive value for VIA (85.1%, 84.1%, 41.7%, 97%), VILI (95.7%, 92.4%, 62.5%, 93.4%) and Colposcopy (83%, 86%, 51.3%, 96.6%) were statistically significant with its histopathological report. Conclusions: In a poor developing country like India where pap smear and colposcopy is not available in low resource setting VIA and VILI can prove a very helpful tool in picking up abnormal looking cervix which can then be confirmed by pap or colposcopy. It will go a long way in reducing the incidence of cervical carcinoma.